Robust Genetic Transformation System to Obtain Non-chimeric Transgenic Chickpea - Das Bhowmik, Sudipta Shekhar; Cheng, Alam Yen; Long, Hao; Tan, Grace Zi Hao; Hoang, Thi My Linh; Karbaschi, Mohammad Reza; Williams, Brett; Higgins, Thomas Joseph V.; Mundree, Sagadevan G. (Frontiers in Plant Science, 2019)
Chickpea transformation is an important component for the genetic improvement of this crop through modern biotechnological approaches. However, recalcitrant tissue culture and occasional chimerism encountered during transformation hinder efficient generation of transgenic chickpeas. Two key parameters, namely micro-injury and light emitting diode (LED)-based lighting were used to increase transformation efficiency. Early PCR confirmation of positive in vitro transgenic shoots, together with efficient grafting and an extended acclimatisation procedure contributed to the rapid generation of transgenic plants. High intensity LED light facilitate chickpea plants to complete their life cycle within 9 weeks thus enabling up to two generations of stable transgenic chickpea lines within 8 months. The method was validated with several genes from different sources, either as single or multi-gene cassettes. Stable transgenic chickpea lines containing GUS (uidA), stress tolerance (AtBAG4 and TlBAG), as well as Fe-biofortification (OsNAS2 and CaNAS2) genes have been successfully produced.